'Personalised nutrition: studies in the biogenetics of race and food'. (4th May 2021) - Sikka, Tina
ABSTRACT: This article articulates a robust study of potentially harmful trend toward personalized nutrition through an examination of contemporary conversations and theories surrounding genetic science, race, identity, health, and food. It makes that case that genetic ancestry kits, and the nutritional recommendations that stem from them, represent a misunderstanding of current genetic science and the capabilities of genetic technologies. I argue that the most troubling outcomes these applications are likely to have is in the further reification and perpetuation of racialized and racializing knowledge and discourses. I also make the case that trends in personalized nutrition are likely to produce yet another locus of inequality based on disparities in access to the 'right' foods, the iniquitous distribution of dietary capital, the further responsibilization of health to individuals, increased surveillance, and a more impoverished and functionalized relationship to food itself.